Program for comprehensive sickle cell disease care in Cuba - Svarch, Eva (Revista Cubana de Hematología, Inmunología y Hemoterapia, 2016)
The prevalence of AS trait in Cuba is 3.04% in the general population. Since 1986-2012, a total of 5042 molecular prenatal diagnosis was performed in pregnant women, and 992 fetuses of sickle cell disease (SCD) were found. Since 1990 a program for comprehensive SCD care was developed in the Instituto de Hematología e Inmunología, the leading Center for SCD in Cuba. Children with severe disease were treated with hydroxyurea at a fixed dose of 15/mg/Kg/day. A significant decrease of painful vaso-occlusive crisis, acute chest syndrome, transfusions and hospital admissions were observed. Transcranial Doppler ultrasonography was performed in 107 children with sickle cell anaemia. When the velocity in the median cerebral arteries was conditional or abnormal, we indicated continuous treatment with HU at a dose of 25 mg/kg/day. A decrease of ratios of full scale intelligence, performance scale, order figures and block design was found. The comprehensive care of SCD in Cuba provided a better quality of life for SCD children. Psychosocial support including genetic counselling and educational and labour orientation are given to all the patients.